The Office - Season One Episode 1-6 - Kwapis, Ken; Whittingham, Ken; Gordon, Bryan; Daniels, Greg; Heckerling, Amy; Smokler, Peter; Einhorn, Randall; Carell, Steve; Wilson, Rainn; Krasinski, John (Universal, 2006)
Steve Carell stars in "The Office", a fresh and funny mockumentary-style glimpse into the daily interactions of the eccentric workers at the Dunder Mifflin paper supply company. Based on the smash-hit British series of the same name and adapted for American Television by Greg Daniels ("King of the Hill", "The Simpsons"), this fast-paced comedy parodies contemporary American water-cooler culture. Earnest but clueless regional manager Michael Scott (Carell) believes himself to be an exceptional boss and mentor, but actually receives more eye-rolls than respect from his oddball staff. [www.amazon.com]
Keywords: DVD-Video